Plant Growth - Cid Rigobelo, Everlon (IntechOpen, 2016)
Over the last few decades, the prevalence of studies about plant growth has dramatically grown in most regions of the world. Many aspects have been investigated related to this phenomenon. If we can gain understanding of how plants grow, then we may be able to manipulate it to reduce both chemical fertilizer use and its environmental impact without decreasing the yield. This book provides information about the use of bio-agents, plant health, plant pathogen, property of melanin, and the influence of rootstock and root growth. We hope this information will be useful for all the people who work with this hot topic.